Застосування проектно-орієнтованого підходу до вдосконалення регіональних систем публічного адміністрування - Гавкалова, Наталія Леонідівна; Власенко, Тетяна Анатоліївна (НТУ "ХПІ", 2017)
Обґрунтовано головні етапи проектно-орієнтованого управління системами публічного адміністрування, що діють за принципами E-Gov 2.0 (на прикладі систем регіональної медицини). Виявлено переваги впровадження системи проектно-орієнтованого управління для держави, бізнесу та інвесторів, окремих організацій та їх клієнтів. Запропоновано рекомендації щодо імплементації системи, а також розглянуті новітні тенденції та технології, що можуть вплинути та можуть бути застосовані.

The major stages of project-based management systems of public administration, acting on the principles of E-Gov 2.0 (an example of regional medicine) are justified. The objectives of the article were implemented by using the following general and specific research methods: analysis and synthesis, systematization and generalization. Advantages of project-based management introduction for government, business and investors, some organizations and their clients are discovered. The recommendations for the implementation of the system re given; the latest trends and technologies that can affect and can be applied are considered. Advantages of project-based management introduction for government, business and investors, some organizations and their clients are discovered. The recommendations on the implementation of, and discussed the latest trends and technologies that affect and can be applied. The implementation of project-based approach to the management of regional public administration system will enhance the overall effectiveness of governance that will have positive consequences for the state, business, potential investors, subordinated organizations and their clients.
Implementation project-based approach to improving regional systems of public administration
Keywords: публічне адміністрування; регіональні системи; електронне урядування; принципи E-Government 2.0; проектно-орієнтований підхід; public administration; regional system; e-governance; principles of E-Government 2.0; project-oriented approach